Need for sustainable architecture - Omer, Spahic (islamicity.org, 2018)
People are both the creators and demolishers of civilizational accomplishments. They are the only beneficiaries of every great civilizational output. Similarly, people are the conceivers, creators and users of architecture -- a physical locus of civilizations. They create architecture and then use and interact with it. They do so either commendably, securing and enjoying the fruits of their rightful acts so long as they stick to the right systems that led them to such a state, or appallingly with no clear purpose or direction. In the latter’s case, things always work against the authors of and heirs to such an architectural tradition as is anchored in flawed worldviews and value systems, making people’s lives despondent and perilous.